Kritik Marcuse terhadap Kultur Konektivitas dan Performatifitas dalam Jaringan (Daring) - Raden Panji Supriyadi; Suharto Suharto; Alexander Seran Bria; Sahrul Ramadhan; Rizky Risdianto (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This paper examines the contributions of Herbert Marcuse's thought to the development of the Critical Theory tradition, particularly through his analysis of the relationship between technological rationality, consumer culture, and structures of domination in advanced industrial societies. Marcuse demonstrates that technological progress is not neutral, but rather embedded in the logic of power that shapes patterns of social consciousness and behavior. Through the concept of the "one-dimensional man," he highlights the mechanisms of homogenizing consciousness that lead individuals to accept social conditions without a critical attitude. Furthermore, Marcuse's synthesis of the ideas of Marx and Freud in Eros and Civilization shows that repression occurs not only in the economic realm but also through the regulation of desire and the body. Imagination and aesthetics are positioned as potential spaces for opening up possibilities for liberation, as both present forms of experience that cannot be fully controlled by the system. By highlighting the relationship between material structures, social psychology, and the production of meaning, this paper reexamines the relevance of Marcuse's Critical Theory for the contemporary context marked by the intensification of digital capitalism and consumer culture.